Color semantics in traditional japanese culture - Югaй М. Р. (Journal of Oriental Studies, 2018)
In different cultures color has several symbolic meanings and is interpreted based on customs and traditions and behavioral norms of the people. Semiotics of color contributes to the opening of the traditional culture fundamentals. The article analyzes conception of color which dominates in Japanese language and culture, and also emphasizes color which is on the pole position. Historic and sociocultural examples mentioned in the article open the idea of color hierarchy in Japanese culture.